How panicle angle and panicle position in the canopy determine pollination and seed set in rice (Oryza sativa L.). (2nd July 2020) - Win, Aung; Tanaka, Takashi S. T.; Matsui, Tsutomu
ABSTRACT: We examined the effect of panicle position relative to canopy and of panicle angle on pollination and floret sterility in rice at anthesis in a paddy field. We set panicles of pot-grown rice at the flowering stage either upright (0°) or inclined (30°), either above or at canopy height (Experiment 1) and either beneath or at canopy height (Experiment 2), in three replications each. In Experiment 1 and Experiment 2, panicle inclination at 30° increased the percentage of florets with <20 total pollen grains on the stigma (TP20) by 21% and 27%, increased the percentage of florets with <10 germinated pollen grains on the stigma (GP10) by 21% and 30%, and increased floret sterility by 10% and 26%, respectively. Floret sterility was correlated with GP10 in all trials. GP10 was correlated with TP20. The effect of position on floret sterility was not significant. We conclude that panicle inclination at 30° significantly increased floret sterility even under the canopy condition. Uprightness of panicles should be an important objective in rice breeding and production. Abbreviations: TP20, percentage of florets with <20 total pollen grains on the stigma; GP10, percentage of florets with <10 germinated pollen grains on the stigma. Graphical Abstract: